(untitled) - Talati, Jamsheer J.; Jamsheer J. Talati (Karachi, 1998)
This book, based on the 1996 Seminar `Higher Education: A Pathway to Development', emphasizes the importance of higher education in cultivating individuals to become leaders of change in the developing world. Regional perspectives, academic offerings, quality, governance, and finance are some of the topics discussed. The book presents the challenges for the 21st century educationalists and ends with the reflections of eminent scholars
Includes bibliographical references and indexes
Keywords: Education (Higher)